2020
DOI: 10.1111/mmi.14448
|View full text |Cite
|
Sign up to set email alerts
|

What makes bacterial pathogens so sticky?

Abstract: Pathogenic bacteria use a variety of cell surface adhesins to promote binding to host tissues and protein-coated biomaterials, as well as cell-cell aggregation. These cellular interactions represent the first essential step that leads to host colonization and infection. Atomic force microscopy (AFM) has greatly contributed to increase our understanding of the specific interactions at play during microbial adhesion, down to the single-molecule level. A key asset of AFM is that adhesive interactions are studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 65 publications
0
19
0
3
Order By: Relevance
“…This has therefore important implication in our view of infection. In the current context of a concerning rise in multidrug resistant pathogens, our work provides new insights that could inspire us in developing anti-adhesive therapeutics 3 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This has therefore important implication in our view of infection. In the current context of a concerning rise in multidrug resistant pathogens, our work provides new insights that could inspire us in developing anti-adhesive therapeutics 3 .…”
Section: Discussionmentioning
confidence: 97%
“…In the context of host colonization, the transition between planktonic and sessile lifestyles plays a functional role in mediating host-microbe interactions. Indeed, attachment to host tissue, more specifically to cells, is often a critical first step towards infection or commensalism 2,3 . As a result, the dynamics of attachment of single bacteria to host cells can dramatically influence the outcome of infection or regulate host-microbiota homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We grew at 1000°C in an O 2 atmosphere a 0.2-μm-thick SiO 2 layer to obtain a hydrophilic surface after the etching step. We observed that bacteria left behind a surface modification of the SiO 2 which prevented stable rewetting of the chip [8,9]. To enable fresh reruns the chip surfaces were cleaned by a wet HF strip of the SiO 2 surface followed by thermal regrowth of the SiO 2 surface.…”
Section: Methodsmentioning
confidence: 99%